Civil Justice and the Limits of Trust: Balancing Integration, National Diversity, and Equality - Savčić, Sanja (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The evolution of judicial cooperation in civil matters within the European Union (EU) reflects the Union’s growing commitment to creating an integrated legal framework that enhances cross-border cooperation and legal certainty. Starting with the Maastricht Treaty in 1993, judicial cooperation was formalised, setting the foundation for later developments. The Amsterdam Treaty (1997) institutionalised cooperation further, particularly through Title IV of the EC Treaty, emphasising the importance of an integrated approach to justice. The Tampere European Council (1999) marked a significant shift, establishing mutual recognition of judgments as a central principle to foster trust among Member States’ legal systems. This principle aimed to simplify the recognition and enforcement of legal judgments across borders, which was seen as crucial for the EU’s objectives of freedom, security, and justice. The Lisbon Treaty (2009) further cemented these efforts by incorporating judicial cooperation into Title V of the Treaty on the Functioning of the European Union (TFEU), aligning it with the ordinary legislative procedure to enhance democratic accountability and efficiency. Despite these advances, the principle of mutual trust remains one of the most ambiguous concepts in EU law, with its exact nature and limits not fully defined, particularly regarding the protection of fundamental rights and varying standards of judicial independence across Member States. Instruments like the Brussels I Regulation and the European Small Claims Procedure have contributed to enhancing access to justice by offering streamlined, efficient mechanisms for resolving cross-border disputes, thus promoting legal certainty and fostering trust in the EU’s legal system. However, challenges remain due to differing national interpretations of mutual trust, which can lead to legal uncertainty and inconsistencies in the application of EU law, particularly when fundamental rights protections vary between Member States. The ongoing evolution of EU legal instruments and jurisprudence from the Court of Justice of the European Union (CJEU) will be critical in addressing these challenges, ensuring that mutual trust and legal protection for individuals are consistently upheld across Member States. However, the EU continues to navigate the balance between legal integration and respect for national legal differences, aiming to strengthen the internal market and enhance the protection of rights across Member States.